Discovery of novel mRNA demethylase FTO inhibitors against esophageal cancer - Bo Qin; Qian Bai; Dan Yan; Fanxiang Yin; Zhu Zhu; Chaoyuan Xia; Yang Yang; Yi Zhao (Journal of Enzyme Inhibition and Medicinal Chemistry)
A series of 1,2,3-triazole analogues as novel fat mass and obesity-associated protein (FTO) inhibitors were synthesised in this study. Among all 1,2,3-triazoles, compound C6 exhibited the most robust inhibition of FTO with an IC50 value of 780 nM. It displayed the potent antiproliferative activity against KYSE-150, KYSE-270, TE-1, KYSE-510, and EC109 cell lines with IC50 value of 2.17, 1.35, 0.95, 4.15, and 0.83 μM, respectively. In addition, C6 arrested the cell cycle at G2 phase against TE-1 and EC109 cells in a concentration-dependent manner. Analysis of cellular mechanisms demonstrated that C6 concentration-dependently regulated epithelial mesenchymal transition (EMT) pathway and PI3K/AKT pathway against TE-1 and EC109 cells. Molecular docking studies that C6 formed important hydrogen-bond interaction with Lys107, Asn110, Tyr108, and Leu109 of FTO. These findings suggested that C6 as a novel FTO inhibitor and orally antitumor agent deserves further investigation to treat esophageal cancer.